Development and Validation of a Tool to Improve Community Pharmacists’ Surveillance Role in the Safe Dispensing of Herbal Supplements - Jairoun, Ammar Abdulrahman; Al Hemyari, Sabaa Saleh; Abdulla, Naseem Mohammed; Shahwan, Moyad; Jairoun, Maimona; Godman, Brian; El-Dahiyat, Faris; Kurdi, Amanj (Frontiers in Pharmacology, 2022)
Background: There has been an appreciable increase in the use of herbal supplements, including immune boosters, during the current COVID-19 pandemic. However, there are concerns with falsified herbal supplements. Objectives: Developed a new questionnaire that can potentially help community pharmacists identify the extent of falsified herbal supplements. Methods: A 9-month cross sectional study was conducted among 500 community pharmacies across United Arab Emirates. A new 5-factor, 24-itmes scale was developed based on current labelling requirements across countries and piloted. This included seven items on identified uses and contraindication, seven items on hazard identification, four items on product identity, three items on packaging and product insert and three items on product handling and storage. The face and content validity of the scale was assessed via the content validity index (CVI). Its construct validity was tested using an exploratory factor analysis (EFA) via principally component analysis (PCA). The model was subsequently confirmed through partial confirmatory factor analysis (PCFA). Its reliability was assessed via test-retest reliability, internal consistency, item internal consistency (IIC), and intraclass correlation coefficients (ICCs). Results: The CVI of the finalized questionnaire was 0.843. The Kaiser-Meyer-Olkin measure of sampling adequacy was 0.891, and Bartlett’s test of sphericity indicated significance (p-value < 0.001). Confirmation of the subsequent 5-domains was achieved through PCFA using maximum likelihood analysis with oblimin rotation. The PCFA obtained values was 0.962 for NFI, 0.977 for CFI, and 0.987 for the Tucker Lewis Index. All values were greater than 0.95, and the RMSEA value was 0.03 (i.e., less than 0.06). Consequently, the model had a good fit. All domains demonstrated Cronbach’s alpha coefficients above 0.70, with 0.940 for the full instrument. Meanwhile, all items met the IIC correlation standard of ≥0.40. The instrument presented good ICC statistics of 0.940 (0.928–0.950) as well as statistical significance (p < 0.001). Community pharmacists with more than 10 experience years were more likely to identify falsified herbal supplements compared to those with 1–10 years experience (p < 0.001). Conclusion: This study developed and validated a new instrument to identify safe herbal supplements, which should enhance the role of the community pharmacists in the safe and effective treatment of suitable patients with herbal supplements.